Agricultural chemicals and the environment : issues and potential solutions - Hester, R. E. (Ronald E.); Harrison, Roy M., 1948-; Royal Society of Chemistry (Great Britain) (Cambridge, UK : Royal Society of Chemistry, 2017)
Agricultural production is in a period of rapid transformation which has seen an increase in the use of biotechnology, synthetic chemistry, biological chemicals and biopesticides. These disciplines are integrated with improvements in application technology, digital farming and the use of big data. Whilst offering unique opportunities to reduce potential environmental impacts, these advances also raise new environmental concerns. This book provides an overview of the changes occurring in the agricultural industry, highlighting opportunities to address impacts and indicating potential barriers to adoption of the technology. This new edition has been updated to include the very latest in agricultural developments, including organic farming and genetically modified crops. It is of interest to students and academics, as well as farmers and landowners and those working in legislation.--
Includes bibliographical references and index.
Keywords: Agricultural chemicals -- Environmental aspects